DO RISK FACTORS DIFFER FOR CONCUSSION AND PROLONGED RECOVERY FOLLOWING CONCUSSION IN ELITE YOUTH ICE HOCKEY PLAYERS?. Issue 7 (11th March 2014) - Blake, T; Meeuwisse, WH; Lemke, N; Schneider, K; Taylor, K; Kang, j; Emery, CA
Abstract : Background: Pediatric concussion risk factor identification will facilitate targeted injury prevention strategy development. Objective: To examine risk factors for concussion and prolonged recovery amongst elite youth ice hockey players. Design: Cohort study. Setting: Community ice rinks and sport medicine clinic (2011/12 season). Participants: Male and female elite Bantam (13–14 years) and Midget (15-17 years) ice hockey players (n=780). Assessment of risk factors: Baseline age group, sex, previous concussion history and SCAT2 component scores [Total Symptom Score (TSS), Balance Error Score (BES) and Standardized Assessment of Concussion (SAC) score] were evaluated. Main outcome measurements: Players with a suspected concussion were referred to a sport medicine physician by team therapists/trainers (n=137). Concussions with time loss of >10 days were defined as prolonged recovery. Results: Concussion incidence rate ratios (IRR) were estimated using multivariate (concussion) and univariate (prolonged recovery) Poisson regression analyses (cluster and exposure hours adjusted). Males were at greater risk than females [IRR=1.44 (95% CI: 1.09–1.90)]. In females with no concussion history, Bantam players were at greater risk than Midget players [IRR=4.04 (95% CI: 1.24–13.19)]. In Midget players, those with a history of concussion were at greater risk than those with no concussion history [IRR=2.68 (95% CI: 1.61–4.46)]. Players with baseline TSS in the lowest 25 th %ile were at greater risk of concussion [IRR=1.50 (95% CI: 1.03–2.18)] and prolonged recovery [IRR=1.88 (95% CI: 1.18–2.99)]. Players with a history of concussion were at increased risk for prolonged recovery [IRR=2.02 (95% CI: 1.29–3.16)]. SAC and BES were not risk factors. Conclusions: Age group, sex, previous concussion history, and baseline symptom reporting affected the risk of concussion and prolonged recovery in elite youth ice hockey players. This study will inform the development of youth sport concussion prevention strategies.